2010
DOI: 10.1002/anie.200906891
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Inorganic–Organic Nanohybrid Materials: Coupling Quantum Dots to Carbon Nanotubes

Abstract: Inorganic meets organic: Covalent bonds (peptide condensation) and noncovalent interactions (π–π stacking) have been employed en route toward versatile donor–acceptor inorganic–organic nanohybrids, QD‐pyrene/SWNT. A charge‐transfer event within the hybrid transforms the excitonic state of the quantum dot into a charge‐transfer state that has a lifetime of several nanoseconds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 32 publications
2
46
0
Order By: Relevance
“…The In–O bonding distance could also increase upon interaction with the residual oxygen functionalities, such as carboxylic acid, at the NCNT surface 36. We note that this is the first QD:CNT hybrid structures without any adhesive ligand between the QDs and the CNTs 37, 38. Without any intermittent layer, barrier‐free charge transfer is expected between the QDs and the NCNTs, whose energy levels are well‐matched (Supporting Information, Figure S1).…”
Section: Solar‐cell‐device Characteristics Including Power Conversiomentioning
confidence: 80%
“…The In–O bonding distance could also increase upon interaction with the residual oxygen functionalities, such as carboxylic acid, at the NCNT surface 36. We note that this is the first QD:CNT hybrid structures without any adhesive ligand between the QDs and the CNTs 37, 38. Without any intermittent layer, barrier‐free charge transfer is expected between the QDs and the NCNTs, whose energy levels are well‐matched (Supporting Information, Figure S1).…”
Section: Solar‐cell‐device Characteristics Including Power Conversiomentioning
confidence: 80%
“…The form‐stable PCMs were synthesized in toluene, and the resulting surface‐modified SWNTs were then added and suspended in this solution by ultrasonication 13. Due to large π – π interactions between the PCMs and the surface‐modified SWNTs, the SWNTs were effectively dispersed and stabilized in toluene 14. Then, the SWNT/PCM composite preparations were performed using simple physical methods of vacuum‐evaporation and further drying for 48 h at 80 °C under vacuum (–0.1 kPa) prior to testing.…”
Section: Resultsmentioning
confidence: 99%
“…For semiconducting SWNT, the corresponding values for conduction and valence bands are at −4.8 eV and −5.4 eV, respectively, and the Fermi level is at −4.4 eV [15]. Quenching of fluorescence of semiconductor QD on attachment to CNT was previously demonstrated for PbS- [11,16], CdSe [15,20,22], ZnO [12], and CdSe-ZnS [27] QD. Though qualitatively quenching the fluorescence of the PbS-QD is demonstrated, a detailed quantitative analysis of the degree of FRET is beyond the scope of this report.…”
Section: Resultsmentioning
confidence: 90%
“…Raman spectroscopy indicated that the D and the G bands were unaltered on attachment. Schulz-Drost et al [20] reported the synthesis of CdTe QD coupled with SWNT. First, CdTe QD stabilized by thioglycolic acid and 2-mercaptoethanesulfonate (MESNA) were synthesized.…”
Section: Introductionmentioning
confidence: 99%